2023
DOI: 10.3390/medicina59030503
|View full text |Cite
|
Sign up to set email alerts
|

The Predictive Value of Monocyte/High-Density Lipoprotein Ratio (MHR) and Positive Symptom Scores for Aggression in Patients with Schizophrenia

Abstract: Background and Objectives: Schizophrenia with aggression often has an inflammatory abnormality. The monocyte/high-density lipoprotein ratio (MHR), neutrophil/high-density lipoprotein ratio (NHR), platelet/high-density lipoprotein ratio (PHR) and lymphocyte/high-density lipoprotein ratio (LHR) have lately been examined as novel markers for the inflammatory response. The objective of this study was to assess the relationship between these new inflammatory biomarkers and aggression in schizophrenia patients. Mate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 84 publications
1
1
0
Order By: Relevance
“…The results of this study showed that aggressive behavior were positively correlated with positive symptoms and childhood traumas in patients with schizophrenia, corroborated by prior investigations [ 31 , 32 ]. Per the assessment, positive manifestations in patients with schizophrenia included delusions, muddled thinking, bizarre behavior, and cognitive inconsistencies, all of which greatly affect how they interpret reality, resulting in extreme frustration, varying mood swings, increased arousal levels, and challenges in controlling actions, ultimately leading to aggressive behavior [ 33 ].…”
Section: Discussionsupporting
confidence: 91%
“…The results of this study showed that aggressive behavior were positively correlated with positive symptoms and childhood traumas in patients with schizophrenia, corroborated by prior investigations [ 31 , 32 ]. Per the assessment, positive manifestations in patients with schizophrenia included delusions, muddled thinking, bizarre behavior, and cognitive inconsistencies, all of which greatly affect how they interpret reality, resulting in extreme frustration, varying mood swings, increased arousal levels, and challenges in controlling actions, ultimately leading to aggressive behavior [ 33 ].…”
Section: Discussionsupporting
confidence: 91%
“…More recently, research has conducted on peripheral blood leucocytes (monocytes, lymphocytes and neutrophils) and lipoproteins (low density lipoproteins, high density lipoproteins) as inexpensive and readily obtainable markers of inflammation in schizophrenia, particularly in assessing the risk of cardiovascular morbidity in such patients. 9 A novel marker indicating subclinical inflammation is monocyte to high density lipoprotein ratio (MHR). In several systemic diseases such as artery disease, cancer and auto-immune disorders MHR has been examined and high values have been linked to increased disease severity, treatment resistance and worse prognosis.…”
Section: Original Articlementioning
confidence: 99%